Managerial payoff and gift-exchange in the field - Florian Englmaier; Stephen Leider (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
We conduct a field experiment where we vary both the presence of a gift-exchange wage and the effect of the worker's effort on the manager's payoff. Results indicate a strong complementarity between the initial wage-gift and the agent's ability to "repay the gift". We control for differences in ability and reciprocal inclination and show that gift-exchange is more effective with more reciprocal agents. We present a principal-agent model with reciprocal subjects that motivates our findings. Our results help to reconcile the conflicting evidence on the efficacy of gift-exchange outside the lab.
Keywords: C91; J33; M52; 330; incentives; field experiments; gift-exchange; reciprocity